Temperature-dependent compressive creep of ferroelectric ceramics and evolution of remnant state variables - Kim, Sang-Joo; Ji, Dae Won (Journal of the European Ceramic Society, 2013)
A pre-poled lead titanate zirconate cube specimen is subject to constant compressive stress of six different magnitudes at four different room and high temperatures. Electric displacement in poling direction and strains in longitudinal and transverse directions are measured and plotted versus time. The effects of stress and temperature on creep behavior of the material are discussed. Then compressive stress of impulse type with gradually increasing magnitude is applied to the specimen and it is found that linear material properties depend linearly on so-called relative remnant polarization at all four temperatures. Using the linear relations, the evolution of remnant state variables during compressive creep is calculated and discussed. Longitudinal and transverse remnant strains are shown to depend linearly on relative remnant polarization, and the relations between relative remnant polarization and applied compressive stress are discussed.